Flow cytometry and cell sorting - Telford, William G. (Frontiers in Medicine, 2023)
While flow cytometry is a critical single cell analytical technique in biomedical science, the technology of flow cytometry associated cell sorting is equally important. Physical separation of cells analyzed by flow cytometry was recognized as an important goal even in the field’s beginning, and many of the earliest cytometers were also cell sorters. Isolation of cells based on flow cytometric analysis has formed the foundation of immune cell differentiation and development and continues to grow importance as techniques for genomic and proteomic analysis expand. This brief review will describe both the historical development and current state of cell sorting. The multiple mechanisms for cell sorters will be covered, and critical aspects of cell sorting will be discussed. Newer technologies for cell sorting including microfluidic technologies will also be considered.